The aphid genus Aphthargelia Hottes (Hemiptera: Aphididae), with one new species - Jensen, Andrew S. (Zootaxa, 2013)
A new species of the previously monotypic aphid genus Aphthargelia is described and the genus reviewed. The new species, A. rumbleboredomia is heteroecious, alternating between host plants in Symphoricarpos and Aconogonon in the mountains of northwestern North America. Descriptive notes on A. symphoricarpi are given, along with diagnostic features for separating the two species of the genus. A key to related genera is presented, and biological information on both species of Aphthargelia is summarized.